Effect of fresnel lens distance on the output power of the prowe plant solar-based electricity transistor 2N3055 - Akbar Nugraha; Caroline Caroline; Ike Bayusari; Rahmawati Rahmawati; Hermawati Hermawati (Control and Computational Intelligent System (CoCIS) Research Group, 2024)
Developments in the human life sector have progressed rapidly today, paralleled by the continuous advancement of technology. This trend is expected to significantly elevate the demand for electricity as one of the primary requirements. Currently, power plants heavily rely on petroleum as their main fuel source for electricity generation, contributing to environmental unfriendliness. In response to this, renewable energy has emerged as a viable solution to reduce dependence on petroleum fuel. One notable example of renewable energy is solar power, harnessed through Solar Power Plants. Research has been conducted to develop a transistor-based solar power plant using the 2N3055 model, with three variations in the distance of the Fresnel lens: 5 cm, 10 cm, and 20 cm over 14 days. The research yielded the highest output power, with an average voltage value of 13.868 V and a current value of 0.000038 A recorded on the 13th day. The power value reached 0.0005199 W on a prototype with a lens distance of 5 cm on the 14th day of research. This phenomenon occurs during sunny environmental conditions, leading to the transistor producing higher voltage and current due to focused light. However, different lens distances can result in improper focusing of light or even prevent light from reaching the transistors altogether, causing suboptimal electricity production or no production. Therefore, the influence of different Fresnel lens distances affects the light focusing on the transistor, consequently impacting the overall power output value.